Strategi Persaingan Harga dan Kualitas dalam Upaya Penaikan Omzet di Toko Online Shaqueena - Ageng Saepudin Kanda S; Rida Natalia Kusumah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Abstrak. The competition in the business world is now increasingly extraordinary. This rapidly changing business situation encourages businesses to respond quickly by switching to consumer tastes and dynamic markets. The number of companies engaged in the same field causes competition to seize the market and difficulties in attracting consumers to buy products marketed by each of these companies. To get customers, companies spend a lot of money to carry out promotional activities. The goal is that customers want to buy the products offered. Companies must be observant in determining market segmentation, choosing target markets, and determining positions in the horizontal era, so that communication strategies are more effective. It is this new strategy concept that changes the application from promotion to communication. Is supported by advances in internet technology, so that the acceleration of information is getting faster and covers a wider area.